Świętożyzna - presumed wife of Świętopełk I - Latoszek, Paweł (Saeculum Christianum. Pismo Historyczne, 2016)
One of the most secretive persons in early medieval Slavia is Świętożyzna. Because her name appears in gospel book of Cividale beside the name of Moravian prince, she is considered to be his wife She is also identified with anonymous bohemian princes, whose wedding conduct was attacked by Franks in 872. Author of this paper tries to connect references of Świętożyzna and find approximate place of her origin including political contacts between Great Moravia and Bohemia in second half of IX century.